Perlindungan Hukum Terhadap Data Pribadi Konsumen Dalam Perjanjian Elektronik (Studi Kasus E-Commmerce Shopee Pada SPX Express di Wilayah Hukum Tembilahan) - Uswatun Khasanah; Fitri Wahyuni; Ali Azhar (Indragiri Law Review, 2025)
This research is motivated by the rapid growth of electronic transactions which is directly proportional to the risk of misuse of personal data. The problem formulations in this research are: 1) What is the form of legal protection for consumer personal data in electronic agreements on Shopee E-Commerce in the Tembilahan jurisdiction? 2) What are Shopee's efforts and responsibilities in ensuring the security of consumer personal data? The research method used is empirical juridical with a legal sociology approach. The results of the study indicate that legal protection has been regulated in Shopee's privacy policy which refers to the PDP Law, however, implementation in Tembilahan still faces data leak obstacles at the logistics operational level. Shopee has implemented security systems such as Two-Factor Authentication (2FA) and SSL encryption, but responsibility for consumer losses still requires strict supervision from the relevant authorities.